Sirt1 inhibits macrophage polarization and inflammation in gouty arthritis by inhibiting the MAPK/NF-κB/AP-1 pathway and activating the Nrf2/HO-1 pathway - Xu Zhao; Menglan Li; Yiwei Lu; Mi Wang; Jiawei Xiao; Qingqing Xie; Xinyi He; Shiquan Shuai (Inflammation Research, 2024)
Objective and design To elucidate Sirt1’s role in gouty arthritis inflammation and its potential mechanisms. Material Constructed murine models of gouty arthritis and conducted THP-1 cell experiments. Treatment 1 mg of MSU crystals injected into mice ankle joints for a 72-h intervention. After a 3-h pre-treatment with Sirt1-specific inhibitor (EX527) and agonist (SRT2104), inflammation was induced for 21 h using lipopolysaccharide (LPS) plus MSU crystals. Methods We assessed gouty arthritis severity through joint inflammation index, swelling, and hematoxylin and eosin (H&E) staining, and measured CD68 mononuclear macrophages and Sirt1 expression in synovial tissue via immunohistochemistry. ELISA, NO assay, RT-qPCR, Flow cytometry, and Western blot were utilized to examine macrophage inflammatory factors, polarization, reactive oxygen species(ROS), MAPK/NF-κB/AP-1 and Nrf2/HO-1 pathways proteins. Results Significant joint swelling, synovial tissue edema, and inflammatory cell infiltration were observed. CD68 mononuclear macrophages and Sirt1 expression were elevated in synovium. Sirt1 activation decreased inflammatory factors, M1 polarization, and ROS generation. Sirt1 activation reduced p38/JNK phosphorylation, thereby inhibiting downstream NF-κB p65/AP-1 and enhancing Nrf2/HO-1, thus suppressing inflammation. Conclusions Sirt1 alleviates M1 macrophage polarization and inflammation in gouty arthritis by inhibiting the MAPK/NF-κB/AP-1 pathway and activating the Nrf2/HO-1 pathway. Thus, activating Sirt1 may provide a new therapeutic target for gouty arthritis.